Generating Discorrelated States for Quantum Information Protocols by Coherent Multimode Photon Addition. Issue 5 (6th April 2021) - Biagi, Nicola; Costanzo, Luca S.; Bellini, Marco; Zavatta, Alessandro
Abstract: It is demonstrated that the recently developed technique of delocalized single photon addition may generate discorrelation, a new joint statistical property of multimode quantum light states, whereby the number of photons in each mode can take any value individually, but two modes together never exhibit the same. By coherently adding a single photon to two identical coherent states of light in different temporal modes, the first experimental observation of discorrelation is provided. The capability of manipulating this statistical property has applications in scenarios involving the secure distribution of information among untrusted parties, like in the so‐called "mental poker" games. Abstract : By coherently sharing a single photon between two weak laser pulses, a quantum light state is obtained that never exhibits the same number of photons in the two modes. Such a "discorrelated" state could be used in quantum information protocols aiming to distribute unique randomness between parties, for example to implement mental‐poker schemes between distant players without the need for a trusted card dealer.